Design and Implementation of Portable and Prospective Embedded System and IoT Laboratory Kit Modules - Era Madona; Yulastri Yulastri; Anggara Nasution; M Irmansyah (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
The purpose of this research is to design and implement a new design of a low-cost, portable and prospective laboratory kit module. Laboratory kits are made easy to assemble, with relatively small dimensions. and suitable for use in laboratories with limited experimental space and funds. The research stages are carried out starting with needs analysis, hardware design, software design and overall testing. The test results of the DHT 11 temperature sensor can read the temperature and humidity index whose data is in the form of digital data and is displayed on the LCD. The PWM of the DC motor and the direction of rotation of the motor can be controlled using the DHT11 sensor. The keypad can control the direction of rotation of the servo motor so that students are expected to be able to provide authentication through a password with a keypad. Testing the module kit for data communication using the local network Testing the module kit for data communication using the local network is able to control the motor and relay even though there is still a delay in sending data this is due to the condition of the internet network at the time of testing. The overall test results work well. It is hoped that this module will encourage students to be able to create technological innovation applications based on embedded systems and IoT which will lead to the creation of technology among students.